Tudo Uni: a laboratorial experience on transmedia production in journalism | DOI: 10.21204/2359-375X/ancora.v3n1p125-143 - TÁRCIA, Lorena (2016)
This report analyses the process of building a multilaboratorial project based on the perspective of transmedia journalism at the University Center of Belo Horizonte (UniBH). It reflects about successes and failures when searching for new ways of gathering, producing and sharing news features across multiple platforms, connecting television, radio, press and web. The results point to behavioral difficulties and resistance from teachers and students in changing production routines rooted in a transmissive media culture.